2006
DOI: 10.1111/j.1365-2249.2006.03049.x
|View full text |Cite
|
Sign up to set email alerts
|

A combination of a transforming growth factor-β antagonist and an inhibitor of cyclooxygenase is an effective treatment for murine pulmonary tuberculosis

Abstract: SummaryTransforming growth factor-beta (TGF-β β β β ) and prostaglandins (PG) regulate the cell-mediated immune response, so it has been proposed that they affect the progression of pulmonary tuberculosis. Here we report that the administration of soluble betaglycan, a potent TGF-β β β β antagonist, and niflumic acid, a PG synthesis inhibitor, during the chronic phase of experimental murine tuberculosis enhanced Th1 and decreased Th2 cytokines, increased the expression of iNOS and reduced pulmonary inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 37 publications
2
42
1
2
Order By: Relevance
“…Up-regulation of MMP-9 expression in murine macrophages by Mycobacterium avium is PGE 2 dependent (39). During the chronic phase of experimental murine tuberculosis, administration of a PG synthesis inhibitor with a TGF-␤ antagonist reduced pulmonary inflammation, fibrosis, and bacillary load (40), consistent with our hypothesis that excess COX-2 activity is associated with immunopathology. Similarly, inhibition of PG accumulation with either aspirin or ibuprofen increased the efficacy of pyrazinamide in a murine model (41).…”
Section: Discussionsupporting
confidence: 87%
“…Up-regulation of MMP-9 expression in murine macrophages by Mycobacterium avium is PGE 2 dependent (39). During the chronic phase of experimental murine tuberculosis, administration of a PG synthesis inhibitor with a TGF-␤ antagonist reduced pulmonary inflammation, fibrosis, and bacillary load (40), consistent with our hypothesis that excess COX-2 activity is associated with immunopathology. Similarly, inhibition of PG accumulation with either aspirin or ibuprofen increased the efficacy of pyrazinamide in a murine model (41).…”
Section: Discussionsupporting
confidence: 87%
“…For example, the inhibition of lung NK cells by alveolar macrophages is through the production of both TGF-␤ and PGE 2 by the macrophages (35). The neutralization of TGF-␤ and the simultaneous inhibition of prostaglandins significantly increased the production of TNF-␣ and NO while inhibiting replication of M. tuberculosis in the lung (36). More recently Woolard et al demonstrated that the elicitation of PGE 2 by LVS contributes to the successful replication of the bacterium in macrophages while suppressing T cell responses in the lung (37).…”
Section: Discussionmentioning
confidence: 99%
“…This might explain why a neutralizing antibody to IL-4 is therapeutic in another highdose challenge mouse model of TB (26) and suggests that reducing IL-4 is likely to be therapeutically useful. Similarly inhibition of TGF-␤ by administering soluble type III TGF-␤ receptors is also therapeutic in this model (12).…”
Section: Discussionmentioning
confidence: 99%